Structural health monitoring using fiber optic sensor - Wang, Wenhao (2018)
Fiber optic sensor is widely used in civil structural health monitoring (SHM) field in the past few decades. One of those made from optical fiber material is Fiber Bragg grating (FBG) sensor, which can indirectly measure strains from wavelength variations. The workability of the conventional FBG sensors, with a serial multiplexing sensing system and data transmission system by interrogators, are examined and assessed in this project through compression tests and flexural tensile tests. Strain gauge readings are used as comparison groups. Both internal embedded FBG sensors and surface mounted ones are used in the testings.